Development of repeated sprint ability in talented youth basketball players - te Wierike, S. C. M.; de Jong, M. C.; Tromp, E. J. Y.; Vuijk, P. J.; Lemmink, K. A. P. M.; Malina, R. M.; Elferink-Gemser, M. T.; Visscher, C. (The Journal of Strength and Conditioning Research, 2014)
Factors affecting repeated sprint ability (RSA) were evaluated in a mixed-longitudinal sample of 48 elite basketball players 14-19 years of age (16.1 ± 1.7 years). Players were observed on 6 occasions during the 2008-09 and 2009-10 seasons. Three following basketball-specific field tests were administered on each occasion: the shuttle sprint test for RSA, the vertical jump for lower body explosive strength (power), and the interval shuttle run test for interval endurance capacity. Height and weight were measured; body composition was estimated (percent fat, lean body mass). Multilevel modeling of RSA development curve was used with 32 players (16.0 ± 1.7 years) who had 2 or more observations. The 16 players (16.1 ± 1.8 years) measured on only 1 occasion were used as a control group to evaluate the appropriateness of the model. Age, lower body explosive strength, and interval endurance capacity significantly contributed to RSA (p < 0.05). Repeated sprint ability improved with age from 14 to 17 years (p < 0.05) and reached a plateau at 17-19 years. Predicted RSA did not significantly differ from measured RSA in the control group (p < 0.05). The results suggest a potentially important role for the training of lower body explosive strength and interval endurance capacity in the development of RSA among youth basketball players. Age-specific reference values for RSA of youth players may assist basketball coaches in setting appropriate goals for individual players.